Evaluation of Effectiveness of Boswellia Dalzielii Ethanol Bark Extract in the Control of Poultry Coccidiosis Experimentally Induced in Vom- Nigeria - G. I. A., Dogo; F. E., , Sa’ayinzat,; Tanko, J. T., Ikpa, L. T.,; Anani, H. M., Fantur, D. Blnjing, R. N, (International Journal of Innovative Research in Medical Science, 2017)
In this study, the effectiveness of Boswellia dalzielli ethanol bark extract was evaluated experimentallywith Sulphachlopyrazine (ESB3™) in the treatment of cecal coccidiosis in broiler chickens in Vom. A total of 28 birds were randomly divided into 4 groups of 7 birds each after being acclimatized in cages. Group A were infected and treated with Boswellia dalzielli ethanol bark extract; Group B, infected and treated with (ESB3™); Group C, infected and not treated (Positive control). All groups were infected with 20,000 sporulated Eimeria tenella oocysts orally each, while Group D was not infected and no treatment as negative control. Results obtained from Groups A and B as 11,300 epg / 1,175 epg and 8,300 epg/3,398 epg oocysts count before and after treatment respectively. Group C were infected and not treated had 9,800 epg as counts. Boswellia dalzielli bark extract incidentally has shown to be more effective compared to sulphachlopyrazine (ESB3™) (Standard Drug) based on oocyst output and in the treatment of poultry coccidiosis induced by Eimeria tenella experimentally.